2007
DOI: 10.1007/s10856-007-3221-4
|View full text |Cite
|
Sign up to set email alerts
|

The construction and characterization of layered double hydroxides as delivery vehicles for podophyllotoxins

Abstract: The aim of this study was to construct PPT-LDH nanohybrids and compare their tumor inhibition effects with that of free PPT. Anticancer drug podophyllotoxin (PPT) was encapsulated in the galleries of Mg-Al layered double hydroxides (LDHs) by a two-step approach. Tyrosine (Tyr) was first incorporated into the interlayer space by co-precipitation with LDH, prop-opening the layers of Mg-Al/LDH and creating an interlayer environment inviting drug molecules. PPT was subsequently intercalated into the resulting mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…(Xue et al, 2007). The purpose of this study was to investigate in vitro and vivo anti-tumor efficiency of LDH as PPT delivery.…”
Section: Introductionmentioning
confidence: 99%
“…(Xue et al, 2007). The purpose of this study was to investigate in vitro and vivo anti-tumor efficiency of LDH as PPT delivery.…”
Section: Introductionmentioning
confidence: 99%
“…28,34 First, Tyr-LDH was prepared via the coprecipitation method under a nitrogen (N 2 ) atmosphere, as is conventional to minimize or avoid contamination by atmospheric CO 2 .…”
Section: Preparation Of Nanohybridsmentioning
confidence: 99%
“…Special interests have focused on exploring the possibilities of using LDH drug delivery systems to deliver antiinflammatory drugs, 31 anticoagulants like heparin, 32 or anticancer drugs. 33,34 These studies involve some basic issues, including the intercalation (loading) of drugs or biomolecules into the LDH interlayer, the release behaviors of drugs or biomolecules from the LDH interlayer under different physiological conditions, the toxicity of LDH materials to cells, the cellular uptake of LDH nanoparticles, and cellular drug delivery tests. Furthermore, this drug delivery system can be modified to target specific cells or organs, thereby expanding its application range.…”
Section: Introductionmentioning
confidence: 99%
“…12 Many studies have demonstrated that anticancer drugs [13][14][15][16] and genes 7,[17][18][19][20] could be successfully intercalated into the LDH layers. They can efficiently enter cells via the clathrin-mediated endocytosis pathway, which is the most common energydependent endocytosis.…”
Section: Introductionmentioning
confidence: 99%